Mattering & Marginality: a study among non-traditional learners at a higher learning institution / Nur Maizura Lin ... [et al.] - Lin, Nur Maizura; Othman, Noor Ahnis; Ahmad Basri, Noraini; Abd Rahman, Hezlin Aryani (UiTM Press, 2022)
The theory of Mattering and Marginality was first formulated in 1981 by Morris Rosenberg and Claire McCullough. It is a form of acceptance of an individual by other people. Mattering is divided into two and they are Interpersonal Mattering and Societal Mattering. Interpersonal Mattering is where a person feels that he or she matters to their siblings, spouse or parents and Societal Mattering refers to a community, learning institution, workplace and others. In this pilot study the Societal Mattering is the focus. This is because the study was carried out at a higher leaning institution. The two objectives of this study looked into Mattering and Marginality among non-traditional learners with regards to their perception towards their peers and faculty at their univeristy. A number of 30 non-traditional learners from a public university took part in this online survey. Mattering Scales for Adult Students in Postsecondary Education was adapted and used to measure the variables; peers and faculty. Interesting implications in the field of Education was found in this study specifically under the concept of Mattering.